Sexual differences in relative length of forewing in Hemerobiidae (Neuroptera). - Makarkin, Nikolai Vladimir; Kholin, Sergey K. (Contributions to Entomology = Beiträge zur Entomologie, 1995)
The differences in relative length of forewing in females and males of twenty Palaearctic species of Hemerobiidae are provided. In ten species the forewing of females is significantly narrower than that of males.